A courtship for the Amish spinster - Chapman, Vannetta (Chapman, Vannetta. Indiana Amish market., 2024)
As the last unmarried girl in her family, Eunice Yoder is given an ultimatum--find a husband or full-time job, or move out. Too independent for a suitor and with no one willing to hire such an unconventional Amish woman, Eunice's future seems set. Until widower and best friend Zeb Mast offers her a deal. He'll pretend to court her if she will help care for his young son. Both believe they are done with romance, but as they begin their arrangement, their pretend courtship starts to feel a little too real...